Detrital Mineral U/Pb Age Dating and Geochemistry of Magmatic Products in Basin Sequences State of the Art and Progress - Winkler, Wilfried; von Quadt, Albrecht (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Dating and geochemical analyses of detrital minerals (mainly zircons) combined with traditional methods, such as heavy minerals and sandstone modes, are a powerful tool in paleogeographic and paleotectonic research and industrial applications.